FUNGSI-FUNGSI TERMODINAMIKA EKSES CAMPURAN BINER ASETONITRIL-METANOL PADA 298,15K (Excess Thermodynamic Functions on Acetonitril-Methanol Binary Mixtures at 298.15K) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Farmasi UGM, 2000)
ABSTRACT The excess thermodynamic functions on acetonitrile-methanol binary mixtures, were determined based on total pressure measurements. The plots of total vapor pressures versus mole fractions data of acetonitrile-methanol, showed that the solutions had positive deviation from the ideal behavior. Therefore, determination of thermodynamic functions, values of activitiy () and activity coefficient (y) were required, and these could be obtained by using Barker method. Acetonitrile-methanol binary mixtures formed molecular complexes of the types ANI, and AM2